Tanggung Jawab PT Jasa Raharja Dalam Klaim Asuransi Terhadap Kecelakaan Lalu Lintas Penumpang Angkutan Umum - Cok Gede Bagus Putra Premana Pemayun; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Analogi Hukum, 2025)
Traffic and road transportation play a very important role in daily human life. One of the risks that can occur in human activities is the occurrence of traffic accidents, which are unexpected and unintentional events on the road involving vehicles with or without users. Other means that cause casualties and property damage. The problems are: 1) What is the legal ratio for public transportation passengers in Article 19 of Government Regulation Number 17 of 1965? 2) How is the responsibility of insurance to passengers as victims of public transportation passenger accidents? The purpose of the study is to determine and analyze the legal ratio for public transport passengers in Article 19 of Government Regulation Number 17 of 1965 and to determine and analyze the insurance responsibility of passengers as victims of public transport vehicle accidents. The method used is the normative law method. This research is regulated in Government Regulation Number 17 of 1965 concerning the provisions for the implementation of the Mandatory Passenger Accident Insurance Fund, which aims to help underprivileged people if they have an accident in public transportation, as well as Law Number 33 of 1964 concerning the Mandatory Passenger Accident Insurance Fund In this case the Government cooperates with PT Jasa Raharja to provide coverage and procedures for insurance claims if public transportation passengers experience accidents.